Seventy-seven keys to the civilization of Japan (Sogensha, 1985)
This book has been put together at the request of the Plaza Hotel with the aim of helping the overseas participants attending the HRI meeting in japan in November 1983 to from an accurate understanding of Japan. Each short chapter relates to a different aspect of Japan's history. The approach has brought into focus both the unique qualities of japan and the Japanese and those they share with other peoples and other lands.